БАНКІВСЬКИЙ СЕКТОР У СИСТЕМІ СОЦІАЛЬНО- ЕКОНОМІЧНОГО РОЗВИТКУ РЕГІОНІВ - Сторонянська, Ірина Зиновіївна; Пухир, Світлана Тимофіївна (Науковий журнал «Світ фінансів», 2017)
Сторонянська І. З., Пухир С. Т. Банківський сектор у системі соціально-економічного розвитку регіонів. Досліджено тенденції розвитку банківського сектору економіки на регіональному рівні та визначено його вплив на розвиток економічних систем регіонів України. Проаналізовано інституціональну забезпеченість регіонів банківськими послугами, а також розглянуто ресурсний потенціал банківського сектору в регіональному розрізі. Проведено порівняльний аналіз показників соціально-економічного розвитку регіонів України та показників розвитку банківського сектору, акцентовано увагу на поглибленні міжрегіональної фінансової диференціації та посиленні тенденції переливання фінансових ресурсів із сектору домогосподарств і малого бізнесу в корпоративний сектор. Визначено основні завдання щодо діяльності банківського сектору для подальшого ефективного соціально-економічного розвитку регіонів. Сторонянская И. З., Пухир С. Т. Экономическая сущность и виды финансовых услуг. Исследованы тенденции развития банковского сектора экономики на региональном уровне, определено его влияние на развитие экономических систем регионов Украины. Проанализировано институциональное обеспечение регионов банковскими услугами, рассмотрен ресурсный потенциал банковского сектора в региональном разрезе. Проведено сопоставление показателей социально-экономического развития регионов Украины и показателей развития банковского сектора. Акцентировано внимание на углублении межрегиональной финансовой дифференциации и усилении тенденций переливания финансовых ресурсов из сектора домохозяйств и малого бизнеса в корпоративный сектор. Определены основные задания в сфере деятельности банковского сектора для дальнейшего эффективного социально-экономического развития регионов. Storonianska I., Pukhyr S. Banking sector in the system of social and economic development of region. Introduction. In conditions of declining economic activity the importance of the problem of determining the ways and mechanisms to encourage economic development increased. Banking sector has the powerful potential to stimulate the economic activity. Purpose. Assessed trends in the banking sector at the regional level and established its influence on the development of economic regions of Ukraine. Results. The trends of the banking sector development of economics at the regional level are researched and its impact on the economic systems of the regions of Ukraine is defined. Institutional provision of regional banking services, hereinafter, is analyzed and the resource potential of the banking sector in the regions is examined. Comparison of indicators of social and economic development of the regions of Ukraine and the performance of the banking sector is conducted. Attention is focused on the deepening of intra-regional differentiation and the strengthening of financial trends of the transfusion of financial resources from the household sector and small business into the corporate sector. The main tasks for the banking sector for further effective socio-economic development of the regions are established. Conclusion. The modern development of the banking system of Ukraine is characterized by excessive interregional differentiation and polarization. The process of outflow of financial resources from poorer regions to more developed reduced their resource base and can not create growth points, affecting the economic development of the state.